Adalimumab and Non-Arteritic Anterior Ischaemic Optic Neuropathy: A Case Report. (October 2014) - Kinard, Krista; Walsh, Jessica A.; Penmetsa, Gopi K.; Warner, Judith E. A.
Abstract Sequential anterior ischaemic optic neuropathy was observed in a patient treated with a tumour necrosis factor α (TNF) inhibitor, adalimumab, for ankylosing spondylitis. He developed decreased visual acuity in the right eye after 17 months of treatment. Findings showed right optic disc oedema with haemorrhages and visual field defect. Adalimumab was discontinued and vision stabilised. After restarting adalimumab, he developed optic neuropathy in the left eye. Findings showed optic disc oedema, with haemorrhages and visual field changes in the left eye. Adalimumab may be associated with optic neuropathy; providers prescribing TNF inhibitors should be aware of optic neuropathy as a potential complication.